Kordofan invaded peripheral incorporation and social transformation in Islamic Africa - Stiansen, Endre; Kevane, Michael (Social, economic, and political studies of the Middle East and Asia, 1998)
This edited volume explores the history, social structure and economy of Kordofan in the Sudan. Representing several academic disciplines, each chapter is concerned with the long-term incorporation - through invasions - of the region into wider socio-political and economic structures.